La mythologie dans l’Hécatombe à Diane - Ternaux, Jean-Claude (Réforme, humanisme, renaissance, 2023)
It has been noted that, in the 1570s, poets make less use of mythology. Yet, nearly half of the poems in Le Printemps, to varying degrees, are marked by ancient fable. In this canzoniere, mythology rarely has a purely ornamental function, when constellations and sea creatures are used to spin the metaphor of amorous navigation. In a traditional way, thanks to it, are evoked the pleasures of love. But, on the one hand, Fortune is hostile; on the other hand, Cupid and the Loves are presented so as to mean the shipwreck of love in which the poet indulges. To denounce the harmful role of the small god of the love, which deserves a lawsuit, the pen of the poet, in a surprising way, comes to dip in the triviality. However, confused with the homonymous goddess, Diane Salviati is well celebrated. The mythology finds then all its vitality: the Lethe allows the oblivion and, wishing to die, the unhappy lover metamorphoses in various ancient figures. Aubigné thus revives the Ronsard of the Amours, but his darker lyricism is more sincere.